If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x = 6x + -11 Reorder the terms: 4x = -11 + 6x Solving 4x = -11 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 4x + -6x = -11 + 6x + -6x Combine like terms: 4x + -6x = -2x -2x = -11 + 6x + -6x Combine like terms: 6x + -6x = 0 -2x = -11 + 0 -2x = -11 Divide each side by '-2'. x = 5.5 Simplifying x = 5.5
| 40=41+x | | 18y-6=-18 | | 18y-6=-10 | | 6p-5=7 | | 30=15x | | t=15x | | 6y^3-7y^2-7y+6=0 | | 20z-1+36=5z+5 | | 30-x=10+0.5x | | 11=21a | | 6m=x | | 4(-2z-5)-7=10 | | 35-6= | | 100*20= | | 3r+10=2(-3r+8) | | (5x-4)3-5(4-3x)=7x+7(3x-4) | | h-13=78 | | 5p-3tq=2 | | 7x-36=3x | | 10x+13=68-x | | 9y^2-12y+1=0 | | 3x+8=2x+20 | | 7(3x+4)=9x-12-x | | 2x+3+4x+2=11 | | 13x-(25+11x)=165-2(4x+10) | | 16x^2-13x=0 | | 5x+37=179 | | 12-3(2x+9)=15 | | 3(6z-1)-4(z+2)=5(z+1) | | 4d+3=8 | | 7x+4x=12 | | -9x-1=71 |